On the selection of control configurations for uncertain systems using gramian-based Interaction Measures. (November 2016) - Castaño Arranz, Miguel; Birk, Wolfgang
Abstract : Highlights: We integrate bounds on Interaction Measures in the design of control configurations. Considering uncertainty may result in robust configurations with larger complexity. Robust configurations can be designed from parametric modes or experiments. Designing configurations from experiments saves modelling efforts. Abstract: A critical step in the control design of industrial processes is the Control Configuration Selection (CCS), where each actuator is associated with a set of measurements which will be used in the calculation of the control action. A possible solution to the CCS problem is given by the gramian-based Interaction Measures (IMs), which are derived from nominal process models. This paper introduces the derivation of uncertainty bounds for a gramian-based IM using models with uncertainty described in multiplicative form. An alternative to this model-based approach is presented, where uncertainty bounds are estimated from a tailored experiment. In addition, a procedure for robust CCS is introduced. This procedure integrates the calculated uncertainty bounds in the design of the control configuration.